ANALISIS PENAMBAHAN PUTIH TELUR SEBAGAI CAMPURAN BETON TERHADAP KUAT TEKAN BETON - Repi Agusman; Masril Masril; Ishak Ishak (Ensiklopedia Research and Community Service Review, 2022)
Eggs are a food ingredient that we often encounter in everyday life which is a source of protein. Eggs are composed of several parts, namely egg shell, egg yolk and egg white. Egg white is a white liquid or often referred to as albumen contained in eggs. Egg white has a bladder consisting of 40% thin egg white and 60% thick egg white which contains 10% protein dissolved in water. This study aims to determine the effect of using egg white as an addition to the compressive strength of concrete. Processing egg whites into concrete as an aggregate for mixing concrete, in order to determine the compressive strength of concrete. This study aims to determine the effect of changes that occur in concrete to the mixture of concrete with egg whites with various egg white compositions with a percentage of 5%, 10%, and 15% of the cement weight. The method used in this study is a qualitative method (Research at Laboratories of Muhammadiyah University of West Sumatra) with a mixture of 5% egg white produces a compressive strength of 94.60 kg/cm2, 10% produces 76.75 kg/cm2, and 15% produces a compressive strength 66.04 kg/cm2 at the age of 28 days. The mixture of egg white makes the compressive strength decrease from normal concrete which has a compressive strength of 251.67 kg/cm2 at the age of 28 days. The planned concrete quality is K 250 Fc '20.75 MPa..  Keywords : compressive strength, egg white, cement, concrete, albumen.